Internalization of negative societal views on old age into self-perceptions of aging: exploring factors associated with self-directed ageism - Ishikawa, Motoko (Frontiers in Sociology, 2023)
Introduction A growing number of research has provided evidence for the negative impact of ageism on older people’s health and well-being. Among the three different manifestations of ageism, namely institutional, interpersonal and self-directed ageism, significant ageism-health associations have been proved to be strongest for self-directed ageism. This supports stereotype embodiment theory, which maintains that lifetime exposure to negative age stereotypes leads to the internalization of ageism as a form of negative attitudes towards own aging and it adversely affects health and well-being in old age. However, little is known about how people internalize negative age stereotypes held in the society into self-perceptions of aging. Methods This study aimed to explore how socially shared beliefs about old age are internalized into self-perceptions of aging focusing on uncovering factors related to self-directed ageism. Data were derived from the survey that had examined citizen’s attitudes towards old age and aging in Finland. Multinominal logistic regression models were performed to examine the association of sociodemographic and contextual factors with different combinations of societal age stereotypes and two indicators of self-perceptions of aging: subjective views on old age and personal feelings of own old age. Results The analyses showed that being female, attaining tertiary education, evaluating poor quality of life and awareness of institutional old age discrimination were related to holding negative views on aging towards both society and oneself. Discussion The findings from univariate and multivariate models suggest that it is not age per se, but structural and cultural circumstances shaped with growing older that turns socially shared negative age stereotypes into negative self-perceptions of aging. Even though the study addressed situations in one country, the findings have an important implication for other rapidly aging societies regarding how social and cultural contexts are closely linked to the formation of self-directed ageism.